(untitled) (Desenvolvimento em Questão, 2026)
This article analyzes how the interorganizational arrangement of the Entreposto Sociobio Pacoval reorganizes the extractive value chain of cumaru almonds in the Pacoval quilombola community (Alenquer-PA), under power asymmetries in non-timber forest product commercialization. We conducted a case study within an action-research design using mixed methods: thematic analysis of qualitative data and descriptive statistics for quantitative records, comparing the chain before and after the warehouse implementation. Results show that, in the previous arrangement, middlemen and immediate liquidity needs reduced price transparency, bargaining power and value capture. After the warehouse was established, supply was centralized, prices paid and traded volumes increased, and local organizational capacity strengthened. Working-capital constraints, reliance on external partners and logistical weaknesses remain. The study highlights the warehouse as a social technology that repositions quilombola communities in the value chain and informs policies to promote non-timber forest product extractivism.